Assessing the CO2 capture potential of seagrass restoration projects. Issue 6 (10th September 2013) - Duarte, Carlos M.; Sintes, Tomás; Marbà, Núria; Wan, Shiqiang
Summary Seagrass meadows are important carbon sinks, and they are experiencing a global decline. Restoration of seagrass meadows provides a strategy to mitigate climate change while conserving these important ecosystems. We examined the long‐term carbon sequestration expected for seagrass restoration programmes by developing a model that combined models of patch growth, patch survival in seagrass planting projects and estimates of seagrass CO2 sequestration per unit area for the five seagrass species commonly used in restoration programmes. The model results indicated that the cumulative C sequestered increased rapidly over time and with planting density to reach an asymptote at a planting density of 100 units ha−1 (or 6 m spacing between units). At this planting density, the modelled cumulative C sequestered ranges from 177 to over 1337 tons CO2 ha−1 after 50 years. The value corresponding to this carbon sequestration suggests that the costs of seagrass restoration programmes may be fully recovered by the total CO2 captured in societies with a carbon tax in place, providing additional ecosystem services derived from the role of seagrasses in providing ecosystem services, such as enhanced biodiversity. Synthesis and applications. Seagrass restoration programmes are economically viable strategies to mitigate climate change through carbon sequestration, particularly in subtropical and tropical island states where land‐based options have a limited scope.